Is vaccination against COVID-19 associated with autoimmune rheumatic disease flare? A self-controlled case series analysis. (1st September 2022) - Nakafero, Georgina; Grainge, Matthew J; Card, Tim; Mallen, Christian D; Nguyen Van-Tam, Jonathan S; Williams, Hywel C; Abhishek, Abhishek
Abstract: Objectives: To investigate the association between vaccination against coronavirus disease 2019 (COVID-19) and autoimmune rheumatic disease (AIRD) flare. Material and methods: Patients with AIRDs vaccinated against COVID-19 who consulted for disease flare between 1 December 2020 and 31 December 2021 were ascertained in Clinical Practice Research Datalink (Aurum). AIRD flare was defined as consultation for AIRD with CS prescription on the same day or the next day. Vaccination was defined using date of vaccination and product code. The observation period was partitioned into vaccine-exposed (21 days after vaccination), pre-vaccination (7 days before vaccination) and remaining vaccine-unexposed periods. Participants contributed data with multiple vaccinations and outcomes. Season adjusted incidence rate ratios (aIRR) and 95% CI were calculated using self-controlled case series analysis. Results: Data for 3554 AIRD cases, 72% female, mean age 65 years and 68.3% with RA, were included. COVID-19 vaccination was associated with significantly fewer AIRD flares in the 21-day vaccine-exposed period when all vaccinations were considered [aIRR (95% CI) 0.89 (0.80, 0.98)]. Using dose-stratified analyses there was a statistically significant negative association in the 21 days after first COVID-19 vaccination but no association after the second or third COVID-19 vaccinations [aIRR (95% CI) 0.76 (0.66, 0.89), 0.94 (0.79, 1.11) and 1.01 (0.85, 1.20), respectively]. On AIRD-type stratified analyses, vaccination was not associated with disease flares. Vaccination without or after severe acute respiratory syndrome coronavirus 2 infection, and with vectored DNA or mRNA vaccines, associated with comparable reduced risk of AIRD flares in the vaccine-exposed period after first COVID-19 vaccination. Conclusions: Vaccination against COVID-19 was not associated with increased AIRD flares regardless of prior COVID-19, AIRD type, and whether mRNA or DNA vaccination technology were used.